Estudio de modalidades presencial y virtual para el aprendizaje de cálculo diferencial, Pedagogía de las Ciencias Experimentales de la UNACH. - Caiza Paucar, José David (2023)
The objective of this research is to analyze the differences that were presented in the virtual and in-person modalities for learning differential calculus during and after the COVID-19 pandemic in the pedagogy career of Experimental Mathematical Sciences and Physics at the National University of Chimborazo in the period 2021-1S to 2022-2S. The questionnaire was divided into two blocks using the survey technique and the instrument to know criteria on the teaching methodology and the perceptions regarding generic competencies on the part of the teacher, with a quantitative approach with a non-experimental design. As a result, it was determined that the students' criteria are similar concerning the teacher in the techniques, resources, and evaluation applied. The academic performance obtained in the virtual and face-to-face modalities was also tested through the hypothesis test with the statistic of MannWhitney U = 0.191, which states that there are no significant differences in the academic performance of the students who attended the 4th semester carried out with the SPSS data analysis tool. The study allows us to conclude that the virtual and face-to-face modalities, according to the teaching methodology and generic competencies, developed the same learning role shared by the teacher in both modalities. Likewise, it is also important to work together within the educational context, especially in how the student perceives the teacher's hard work.